Variable stiffness element by granular jamming (Stiffness enhancement by a wrinkle-free outer membrane) - Yuma KITAGAWA; Takashi MITSUDA (Nihon Kikai Gakkai ronbunshu, 2017)
A flexible bag containing particles becomes rigid when the air inside the element is evacuated. Variable stiffness elements using granular jamming have been used for haptic displays and robotic orthoses helped by the soft and lightweight body. However, deforming variable stiffness elements causes wrinkles on the membrane, which decrease and destabilize the stiffness of the element. The wrinkles on variable stiffness elements are due to the non-stretchability of the outer membrane. A stretched membrane reduces wrinkles but decreases the stiffness of the element dramatically. This study suggests a wrinkle-free variable stiffness element with an outer membrane that is stretchable but rigid only when the air inside the element is evacuated. The amount of particles inside conventional elements limits the deformable range of the elements. On the other hand, the novel stiffness element can hold more particles without any loss of the deformable range, which increases the stiffness of the element. The stretchable outer membrane also reduces undesirable deformations of the element caused by wrinkles when the air inside the element is evacuated. The experimental results of this study confirm that the stiffness of the wrinkle-free variable stiffness element is greater and more stable than a conventional stiffness element.